â€œBELI INDONESIAâ€ MOVEMENT AS BREAKTHROUGH TO MANAGE THE PEOPLE'S ECONOMY IN THE MIDDLE OF LEGAL DEADLOCK IN INDONESIA - Trenggono, Heppy (Jurnal Pembaharuan Hukum, 2022)
Beli Indonesia can be said to be a political movement, when viewed from a simple political understanding. Politics builds perceptions in order to gain power. The "Beli Indonesia" movement, a purely economic system is not enough to ward off the invasion of foreign products, but a kind of development of positive Indonesian sentiment is needed in all circles. In the midst of the increasingly swift currents of globalization, in the midst of the industrial revolution 4.0 which gave birth to changes in people's economic behavior, in the midst of China's rise which has awakened the awareness of nationalism in the world's nations, we are called to make a real contribution, to contribute to educating the nation. Article 33 of the 1945 Constitution states that the populist economic system is a system for making people sovereign in the economy. The economic system mandated by our constitution is an economic system that involves the widest possible participation of the people, not a monopolistic economic system, not an economic system that accommodates the greed of a few people. Form Beli Indonesia by defending the economy of our own nation's children.